Quality management system for a collaborative platform. Cafam University Foundation (Revista Electrónica Calidad en la Educación Superior, 2022)
This document presents the proposal for an information management protocol of the internal quality assurance system (SIAC) in Unicafam, whose general objective was the systematization, management and use of information to develop improvement measures based on quality indicators. achievement generated by the institution and by the higher education information systems. In relation to the elements object of analysis for the corresponding purposes were Macroprocesses; self-appraisal; evaluation; self-regulation and information systems. This proposal was justified by the institution's need to establish precise rules about the use of the collaborative platform, as well as to specify the roles that the interested parties have in the internal quality management systems. Methodologically, it was a feasible study based on a field study. It is concluded that the protocol is pertinent to existing regulations and to the internal quality assurance system at Unicafam.
Keywords: Collaborative platform; internal management system; quality management; self-assessment; information systems